La problématique de la représentation des paysages brésiliens dans les manuels scolaires français - Leonardo Moreira Ulhôa; Vânia Rúbia Farias Vlach (Confins)
This text proposes a number of ideas to raise the issue of the representations of Brazilian landscapes in French textbooks,especially the used in the  iconography of geography textbooks. This is a research still in progress, but it is already possible to extract elements for decoding the meanings attributed retrospectively to Brazil's  landscapes in France.